A practical framework for the design of resistance exercise interventions in oncology research settings—a narrative review - Fairman, Ciaran M. (Frontiers in Sports and Active Living, 2024)
Resistance exercise (RE) has been demonstrated to result in a myriad of benefits for individuals treated for cancer, including improvements in muscle mass, strength, physical function, and quality of life. Though this has resulted in the development of recommendations for RE in cancer management from various international governing bodies, there is also increasing recognition of the need to improve the design of RE interventions in oncology. The design and execution of RE trials are notoriously complex, attempting to account for numerous cancer/treatment related symptoms/side effects. Further, the design of exercise trials in oncology also present numerous logistical challenges, particularly those that are scaled for effectiveness, where multi-site trials with numerous exercise facilities are almost a necessity. As such, this review paper highlights these considerations, and takes evidence from relevant areas (RE trials/recommendations in oncology, older adults, and other clinical populations), and provide a practical framework for consideration in the design and delivery of RE trials. Ultimately, the purpose of this framework is to provide suggestions for researchers on how to design/conduct RE trials for individuals with cancer, rather than synthesizing evidence for guidelines/recommendations on the optimal RE dose/program.